Diagnosa Jenis Hama Yang Merusak Tanaman Titi (Gmelina moluccana Blume) Pada Demplot Sumber Benih Desa Hatusua: Diagnosa of Pests that Attack Titi (Gmelina moluccana Blume) Plants in the Hatusua Village Seed Source Demonstration Plot - Teweloipaky, Wasty Yolanda; Wattimena, Cornelia. M.A.; Latumahina, Fransina Sarah (HUTAN TROPIKA, 2024)
Identification of Pests That Attack Titi Plants (Gmelina moluccana Blume) in the Seed Source Demonstration Plot in Hatusua Village. This research aims to determine the types of pests that attack Titi (Gmelina moluccana Blume) plants in the seed source demonstration plot of Hatusua Village, determine the intensity of damage caused by pest attacks and determine the extent of pest attacks that attack Titi (Gmelina moluccana Blume) plants in the Village Seed Source Demonstration Plot. Hatusua. The research was conducted using quantitative descriptive methods, namely making direct observations in the Titi (Gmelina moluccana Blume) plant area. The research results showed that there were three types of pests found on Titi in the Hatusua Village Seed Source Demonstration Plot, namely wood grasshoppers (Valanga nigricornis), tree termites (Neortemes tectonae) and leaf beetles (Phaedonia inclusa Stall). The damage caused by woodhopper pests amounts to 18.86%, tree termites 6.02 %, and leaf beetles 10.54%, and these three pests are included in the mild category. 49,19% of the attack area was caused by woodchoppers, which were in the heavy category; 45.90% were caused by leaf beetles, which were in the medium category, and 4.91% were in the light category